Application of the method of recurrent diagrams to the analysis of signs of x-ray sun radiation - Alimgazinova, N.Zh.; Naurzbaeva, A.Zh.; Manapbaeva, A.B.; Ikramova, S.B.; Kurmangazina, M.B.; Kenzhegaraeva, A.D.; Adilzhan, K. (Recent Contributions to Physics, 2018)
The paper shows the application of a new method of time series analysis based on the fundamental property of dissipative dynamical systems – recurrence, for X-ray signals of the Sun. The method of recurrent diagrams is a graphical tool by which it is possible to identify a number of basic structures responsible for a particular character of system development. The object of investigation is solar X-ray data recorded by the GOES-15 spacecraft. As a result of the research, it was revealed that the recurrent diagram method more clearly captures features and discovers changes (periodicity) in a non-stationary uneven time series. It is shown that, according to recurrent diagrams, soft X-ray radiation gives more information about the processes occurring on the Sun than hard X-ray radiation. It is shown that the intensity values of the X-ray radiation decrease in 2017 as compared with previous years. Analysis of the diagrams of recurrence measures revealed that there are no sharp changes in the values of the recurrence measure in comparison with previous years in 2017, while the average values do not capture it, i.e. In this period, large and powerful flare processes were not observed. The constructed recurrence signal diagramsreveal features and periodicity in the nonstationary nonuniform time series of X-ray radiation.
Keywords: X-ray radiation, nonlinear analysis, recurrent diagram, topology, texture, measure of recurrence